The Effect of Competence, Work Motivation, and Work Discipline on Employee Performance at PT Pelayaran Kartika Samudra Adijaya - Misbahuddin Misbahuddin; Imal Istimal (Jurnal Indonesia Sosial Sains, 2026)
Employee performance is a critical factor in determining organizational success, particularly in service-based industries such as shipping, where operational efficiency and discipline are essential. However, differences in these factors often result in varying levels of employee performance. Therefore, understanding how these variables influence employee performance is important for companies in developing appropriate human resource management strategies. This research aims to analyze the effect of competence, work motivation, and work discipline on employee performance at PT Pelayaran Kartika Samudra Adijaya. This research uses a quantitative approach with a survey method, involving permanent employees of the company as respondents. Data was collected through questionnaires and analyzed using regression tests to examine the relationships between variables. The results show that competence and work motivation significantly influence employee performance, while work discipline acts as an intervening variable that strengthens these effects. This research provides theoretical and practical contributions for the company, especially in developing human resource management policies that can improve employee performance through enhanced competence, work motivation, and work discipline